AN EXPLORATION OF STUDENTS ENGAGEMENT IN EFL ASYNCHRONOUS CLASS - Emiliasari, Raynesa Noor; Nurhidayah, Yayah; Putri, Sopiah Jamaliah Supriadi (Premise: Journal of English Education and Applied Linguistics, 2023)
Students' engagement is an ongoing concern for educators because of its positive association with deep learning, educational purpose, and educational outcomes. The purpose of this study is to reveal the students' engagement and to explore the factors of students' engagement in EFL asynchronous classes. This research was qualitative design with a case study approach. The participants of this study were 35 ten-grades students in one of the senior high schools in Majalengka. Survey and interviews were used to gain the data from the participants. The survey was conducted to 35 ten-graders which focused on their engagement during the asynchronous class as well as their reasons for being to or not engaging with the lessons. Meanwhile, factors that influenced their engagement in the asynchronous class were elaborated using the interview. The result showed that students gave positive responses in students engagement on cognitive and behavioral engagement, most of the students both high and middle achievers always follow the teacher's instructions and sometimes give opinions/ideas. The most prominent factors that influence student engagement is teacher factors, among them are interesting teaching method and teachers' characteristic This study suggests that teachers need a variety of methods in which to use online platforms and conduct more creative activities in order to get the best learning outcomes.Keywords: Asynchronous Learning, EFL Class, Student Engagement.